PENERAPAN TATA KELOLA DESA MELALUI PENDEKATAN PEMBANGUNAN ZONA INTEGRITAS DESA (ZiDes) DI DESA MATA WAWATU KECAMATAN MORAMO UTARA KABUPATEN KONAWE SELATAN - La Ode Anto; Fitriaman Fitriaman; Syamsir Nur; Ika Maya Sari; Waode Aswati; Omasrianto Omasrianto (CV. ALIM'SPUBLISHING, 2024)
This study examines the implementation of village governance through the Zona Integritas Desa (ZiDes) approach in Mata Wawatu Village, Moramo Utara District, South Konawe Regency. The ZiDes program aims to enhance transparency, accountability, and community participation in village governance, as well as to reduce the potential for mismanagement of village funds. This research employs a qualitative descriptive method, which includes literature review, in-depth interviews with village officials and community members, field observations, and documentation analysis. The findings indicate that the implementation of ZiDes has successfully improved village governance through increased transparency, strengthened accountability, and more active community participation. However, challenges remain in terms of human resource capacity and raising community awareness.